Synthesis, Structures and Magnetic Properties of CuII and CoII Compounds Based on Asymmetric 5‐(1H‐Imidazole‐1‐yl)‐3‐pyridine Carboxylic Acid. Issue 39 (30th July 2020) - Li, Jinpeng; Khan, Misbha Rafiq; Liu, Bin; Niu, Xiaoge; Li, Bohan; Hao, Yaping; Liu, Zhongyi
Abstract : Five coordination compounds [Cu2 (impc)2 (µ2 ‐OH)Cl] n (1 ), [Cu2 (impc)2 (µ2 ‐OH)Br] n (2 ), [Co(impc)2 (H2 O)2 ] n (3 ), [Co4 (impc)4 (SO4 )2 (H2 O)] n (4 ) and [Co(impc)(H2 O)2 ]· H2 O (5 ) based on asymmetric 5‐(1 H ‐imidazole‐1‐yl)‐3‐pyridinecarboxylic acid (Himpc) have been hydrothermally synthesized and structurally characterized. 1 and 2 are isostructural and consist of binuclear Cu II units and display two‐dimensional (2D) framework, where 1 and 2 present a new (4.6 2 )(4 2 .6 5 .8 2 .10)(4) topology. 3 features a 1D chain structure. Polymer 4, which also displays a new Schläfli symbol (4 13 .6 20 .8 8 .10 4 )(4 3 )2 (4), contains tetranuclear Co II cluster and is a 2D structure. The planar‐type tetranuclear Co II cluster with SO4 2– bridge in 4 has not been reported. Compound 5 possesses a mononuclear structure. Magnetic susceptibility studies for 1 and 2 with Cu2 units reveal the antiferromagnetic coupling with J = –3.42 cm –1 for 1 and J = –3.83 cm –1 for 2 . Contrary to the only example of class F2 ferromagnetic VII, 1 and 2 (class F2) exhibit different antiferromagnetic behavior. Compounds 3 and 5 exhibit ferromagnetic behavior, and their M(H) curve is consistent with the ferromagnetic nature. No peaks are observed in the out‐of‐phase ( χ'' ) plots of 3, suggesting no long‐range order and no spin canting. For 4 with the Co4 units, it also exhibits ferromagnetic behavior, and the M ( H ) curve is consistent with the ferromagnetic nature. Abstract : Five coordination complexes [Cu2 (impc)2 (µ2 ‐OH)Cl] n (1 ), [Cu2 (impc)2 (µ2 ‐OH)Br] n (2 ), [Co(impc)2 (H2 O)2 ] n (3 ), [Co4 (impc)4 (SO4 )2 (H2 O)] n (4 ) and [Co(impc)(H2 O)2 ]· H2 O (5 ) based on asymmetric 5‐(1 H ‐imidazole‐1‐yl)‐3‐pyridine carboxylic acid (Himpc) have been hydrothermally synthesized and structurally characterized. Compounds 1 –5 display intriguing topologies and interesting magnetic properties.